Taxonomy and phylogeny of the genus Trichopelma Simon, 1888 (Araneae: Theraphosidae: Trichopelmatinae) in Cuba, with the descriptions of seven new species and a new species of Thalerommata Ausserer, 1875 - Ríos Tamayo, Duniesky (2024)
The spiders of the genus Trichopelma Simon, 1888 present in Cuba, are revised. Currently, the genus Trichopelma comprises 22 known species distributed in the Caribbean, and Central and the upper region of South America. Cuba currently hosts five valid species and, in this study, the descriptions of seven new species distributed throughout the island are presented: T. baracoense sp. nov. (♂♀, Guantanamo prov.), T. cheguevarai sp. nov. (♂, Ciego de Ávila prov.), T. citma sp. nov. (♀, Granma prov.), T. fidelcastroi sp. nov. (♂♀, Holguín prov.), T. granmense sp. nov. (♂♀, Granma prov.), T. rudloffi sp. nov. (♂♀, Holguín prov.) and T. soroense sp. nov. (♂♀, Artemisa prov.). Based on morphological characters, a cladistic analysis was performed, revealing the phylogenetic position of the new species compared to the species previously described. Based on this phylogeny, morphological characters and close proximity in distribution, T. banksia Özdikmen & Demir, 2012 syn. n., is proposed as a junior synonym of T. cubanum (Simon, 1903). The genus Thalerommata Ausserer, 1871 is reported from Cuba for the first time, with the description of T. anae sp. nov. (♂, Sancti Spíritus prov.).